Micro-addition of Fe in highly alloyed Cu-Ti alloys to improve both formability and strength. (January 2022) - Rouxel, B.; Cayron, Cyril; Bornand, Julien; Sanders, Paul; Logé, Roland E.
Graphical abstract: Highlights: Cu-6Ti-Fe alloy provided a very high yield strength of 975 MPa after aging, without preformation. Micro-addition of Fe to Cu-Ti alloys supresses the « wave-like » nano-precipitation of Ti occurring after solution annealing and quench. Micro-addition of Fe to Cu-6Ti alloys doubles the formability of the solution annealed state. Nano precipitates oriented in the 〈1 1 0〉 directions were observed for the first time in a Cu-Ti-Fe alloy. Abstract: Cu-Be alloys provide excellent electrical and mechanical properties, but present serious health hazards during manufacturing. Among alternative alloys, the Cu-Ti system has the highest yield strength; however, Ti cannot be easily solutionized at concentrations above 4 wt%, resulting in a relatively low formability. In this study, Cu-xTi-yFe (x = 3, 5, 6 wt% and y = 0, 0.3 wt%) alloys were studied after both solution-annealing and age-hardening through mechanical testing and microstructure analysis. Micro-additions of Fe kept high concentration of Ti in solid solution (up to 6 wt%) after water quenching and suppressed the classical "wave-like" early-stage precipitation. Instead, a new dispersion of nano precipitates was observed. This behavior results in doubling the ductility in the solution annealed state (up to 48% elongation), together with maintaining a very high strength after ageing (up to 975 MPa) from precipitation of metastable nano α-Cu4 Ti. This study shows that Fe micro-additions, when combined with a higher amounts of Ti (6 wt%), enables the production of Cu-based alloys combining high formability and strength, providing an excellent alternative to Cu-Be in mechanical applications.